PROFITABILITAS, PERTUMBUHAN PERUSAHAAN, UKURAN PERUSAHAAN DAN LIKUIDITAS: APAKAH MEMPENGARUHI NILAI PERUSAHAAN? [PROFITABILITY, COMPANY GROWTH, COMPANY SIZE AND LIQUIDITY: DO THEY AFFECT COMPANY VALUE?] - Enjelie, Widya; Anggraeni, Desy (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2024)
This study aims to determine the effect of profitability, company growth, firm size, and liquidity on firm value in food and staples retailing, beverage companies listed on the Indonesia Stock Exchange for the period 2018-2022. The sampling technique used is purposive sampling, the company sample obtained consists of 45 companies. The analysis technique used in this reserch is multiple linear regression. The results of the analysis show that profitability and liquidity has a positive and significant effect on firm value, company growth has no effect on firm value, and firm size has a negative and significant effect on firm value.